Effect of IBSC Learning Model with Qreatif Educative App on Students’ Collaboration Skills - Pratiwi, Vita; Atikah Syamsi; Nur Atikoh (Indonesian Journal of Islamic Elementary Education, 2025)
The 21st century competency that students must have is collaboration skills. Students' collaboration skills in grade IV, especially in science subjects, are still low and also still use conventional learning, namely lectures, in which the teacher is more active in the learning process. Therefore, an interesting learning model or media is needed, to overcome this problem, researchers used the Investigation Based Science Collaborative (IBSC) model assisted by Qreatif Educative game learning media which was designed by integrating investigative and collaborative approaches with the aim of facilitating students in collaborating and communicating. This study aims to (1) determine the effect of the Investigation Based Science Collaborative (IBSC) learning model assisted by Qreatif Educative game learning media on students' collaboration skills in grade IV MIN 1 Cirebon (2) determine the differences in collaboration skills in grade IV MIN 1 Cirebon. This study used a quasi-experimental method with a non-equivalent control group design. The subjects used in this study were class IV A with 28 students and VB with 29 students. Data collection techniques used in this study were collaboration skills questionnaires, observation and documentation. The results of this study showed a significant difference between collaboration skills in the experimental class and the control class, namely 0.014 < 0.05. This proves that the IBSC model assisted by Qreatif Educative games learning media has a positive influence on students' collaboration skills.